The Effect of Social-economic background on electric and electronic waste (e-waste) management amongst Residential areas in Kota Kinabalu City, Sabah, Malaysia - Mapa, Mohammad Tahir; George, Fionna; Peters, Diana; Dinggai, Molia Sebi; Jafar, Adi (The journal of contemporary issues in business and government, 2021)
Electrical and electronic waste (e-waste) is a very complex waste because it contains harmful and harmless chemicals. The toxic chemical properties and heavy metals are very harmful to humans and the environment. Therefore, e-waste needs to be managed efficiently and systematically. Currently, e-waste management in most countries relies heavily on law and does not take into account the culture and socio-economy of the local community. Therefore, this article will identify e-waste management practices among households and analyse the relationship between selected background and household e-waste management in Kota Kinabalu City. The survey method is used as a method of data collection using the questionnaire as the main instrument. The data is analyzed using descriptive statistics (frequency analysis and cross tabulation) and inference statistics (chi square and logistic regression). The total number of respondents obtained was 395 people. The results of the study found that the practice of storing, disposing of bins and selling used items is a popular management method among the households rather than sending e- waste to recycling centres. The study also found that socioeconomic backgrounds such as gender, age and monthly household income have a significant influence on the way e-waste management is conducted. Therefore, this study proves there is a need to emphasize the socio- economic background in managing e-waste, especially in residential areas.